Strategi Problem Based Learning (PBL) Sebagai Upaya Transformasi Pembelajaran Qur’an Hadist yang Kritis dan Reflektif Bagi Mahasiswa PAI Semester 3 - Akbar Dafi Isworo Putra; Siti Wahyuni; Zaenal Arifin (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to analyze the implementation of the Problem-Based Learning (PBL) strategy as an effort to transform Qur’an Hadith learning into a more critical and reflective process for Islamic Education (PAI) students. The background of this study is rooted in the need for Qur’an Hadith learning that is not only oriented toward textual understanding but also develops analytical skills, problem-solving abilities, and contextual Islamic reflection. The method used is library research and conceptual analysis of various literatures related to PBL, critical pedagogy, and Qur’an Hadith learning. The findings indicate that PBL encourages students to engage actively through the identification of contemporary religious issues, examination of relevant Qur’anic verses or hadiths, and the formulation of solutions grounded in Qur’anic values. In addition, this strategy strengthens students’ critical thinking skills, collaboration, and reflective abilities in understanding Islamic texts more profoundly. In conclusion, PBL is an effective approach for transforming Qur’an Hadith learning into a more dialogic, contextual, and problem-solving-oriented process within the Islamic educational perspective.